Main causes of death in children and adolescents in Brazil: Analysis from 2011 to 2020 (Revista Contexto & Saúde, 2024)
Childhood and adolescence are unique stages in human development. However, many children and adolescents are exposed to morbimortality risks, which leads to early deaths. The present study aims to analyze the main causes of death in children and adolescents, aged 1 to 19 years, in Brazil, reported between 2011 and 2020. This is a quantitative, descriptive study, carried out from the secondary data obtained from the DataSUS platform. The period from 2011 to 2020 was used, with a geographical coverage of all regions of Brazil stratified by age group, sex and causes of deaths. The data were submitted to simple statistical analysis through Excel. The four age groups analyzed presented “external causes” and “neoplasms” as the main causes of death. Moreover, males are predominant in deaths of all age groups, with an emphasis on adolescence. Thus, it is emphasized that the mortality rates of children and adolescents can be reduced. In this perspective, the importance of developing public policies on disease prevention, health promotion, access to health services, reduction of social inequalities and public security is pointed out.
Keywords: Child; Adolescent; Death; Nursing